Spontaneous Recanalization of Traumatic Transverse Sinus Occlusion despite Persistence of Depression Fracture - Ozturk, Sait; Cakin, Hakan; Kaplan, Metin (Georg Thieme Verlag Kg, 2015)
A 7-year-old boy was admitted to the emergency department after a closed head injury. Physical examination revealed no neurological disturbances or scalp laceration. Computed tomography revealed depressed skull fracture on the right occipital bone with multiple fracture lines over the right transverse sinus. Magnetic resonance imaging revealed right transverse sinus thrombosis, and magnetic resonance venography identified total occlusion of the right transverse sinus due to bone compression. Despite the presence of venous sinus injury secondary to a depressed skull fracture, surgery was not indicated for this patient. Despite persistence of a right occipital depression fracture identified during a three-dimensional cranial computed tomography performed in the third month following the trauma, the patient's magnetic resonance venography showed spontaneous recanalization of the right transverse sinus. It was demonstrated that venous sinus occlusion secondary to a depressed fracture could heal spontaneously and independently of bone pathology. With such characteristics, this report represents an extremely rare case.
Keywords: closed head injury; depression fracture; occlusion; recanalization; ]transverse sinus